Doornroosje. (Gent vanaf (1985) 7 : Antwerpen : Trefcentrum SadoMasochisme vanaf (1985) 7 Doornroosje, 1983)
Fonds Suzan Daniel (FSD)
Periodiciteit : onregelmatigRedactie : PB 44, 9000 Gent 1 ; vanaf (1985) 7 : Consciencestraat 65, 2018 Antwerpen
Nederlands
Periodiek